Bodied leaf mutants in flue-cured virginia tobacco (Nicotiana tabacum) - RAO, S K; RAMAKRISHNAYYA, V (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1985-91 with 'Kutsaga 51E' flue-cured virginia tobacco (Nicotiana tabacum L.) by inducing mutalion with sodium azide, isolating mutants with localized hyperplasia on abaxial surface of the leaves. These hypciplastie regions are visible as minute outgrowths. On the basis of the extent of hyperplasia, the mutants were of 3 types, viz mildly covered with minute outgrowths, moderately covered with minute outgrowths and highly covered with minute outgrowths. All these mutants are true breeding. The mutants showed differences in thrir expression of leaf body (thickness) and frequency of hyperplastic sites, which conferred the leaves - on flue-curing - higher graininess andnicotinc. These mutants have useful characters such as body, graininess, higher nicotine and yield and hence are economically important.